2002
DOI: 10.1002/fld.356
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic mesh adaptation: towards user‐independent, mesh‐independent and solver‐independent CFD. Part II. Structured grids

Abstract: SUMMARYThe present paper is the second article in a three-part series on anisotropic mesh adaptation and its application to (2-D) structured and unstructured meshes. In the ÿrst article, the theory was presented, the methodology detailed and brief examples given of the application of the method to both types of grids. The second part details the application of the mesh adaptation method to structured grids. The adaptation operations are restricted to mesh movement in order to avoid the creation of hanging node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…Numerous examples have shown that long and thin elements are useful in computation of problems with boundary or internal layers [1,2,14,15,19,22]. A practical question is in what direction an element should be long and how long and thin it should be.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples have shown that long and thin elements are useful in computation of problems with boundary or internal layers [1,2,14,15,19,22]. A practical question is in what direction an element should be long and how long and thin it should be.…”
Section: Introductionmentioning
confidence: 99%
“…⊲ anisotropic mesh adaptation techniques, generating anisotropic elements (i.e., long and thin triangles), which are suitable in computation of problems with boundary or internal layers, see, e.g., [1], [2], [9], [14], [16], [20], [21], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of other size distribution methods include physical analogies such as the spring analogy [3,4] and particle potential minimization [5], methods based on the elliptical Poisson system [6,7,8,9] as well as "center of mass" methods [10,11]. These methods have been used in adaptive setting: they all have some kind of weight function or concentration function that allows for spacing or size specification.…”
Section: Mesh Optimization By Smoothingmentioning
confidence: 99%
“…The concepts of Riemannian metrics and non-conformity are explained next, in Sect. 3. The paper then goes on to explain the smoothing method used to optimize the non-conformity of a mesh (Sect.…”
Section: Introductionmentioning
confidence: 99%